Distribuição espacial e plano de amostragem sequencial para Piezodorus guildinii (Westwood, 1837) (Hemiptera: Pentatomidae) na cultura de soja transgênica RR® - Santos, Leticia Serpa dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Stinkbugs are the main group of soybean insect pests, and among the species that cause losses in yield and quality, Piezodorus guildinii is the most important one. The objective of this work was to determine the spatial distribution of different ninfal instars and adults of P. guildinii in RR transgenic soybean cultivar, and make sequential sampling plans to grains and seeds.The experiment was carried out in Jaboticabal, SP, Brazil, during the 2012/2013 cropping season. It was chosen one of 30-hectare of commercial field, and then it was divided into 100 sampling units of 10 x 10 m each one. It was used the cultivar SYN 9070 RR, which is tolerant to glyphosate. It was recorded the number of nymphs from 1st to 5th instars, as well as, adults by the drop-cloth method. In order to study the dispersion of insects in the field, the following indexes were obtained: variance-to-mean ratio, Morisita’s Index, Green’s Coefficient, and k exponent of negative binomial distribution. To study the probabilistic models that describe the spatial distribution of insect pests, the data were fitted to Poisson and binomial distributions. It was concluded that nymphs of 1st-3rd, 3rd, 4th-5th instars; adults; and 4th, 5th instars plus adults had an aggregated distribution in experimental field, and the negative binomial distribution was the best probabilistic model for nymphs and adults of P. guildinii. There were returned sequential sampling plans of nymphs of 4th and 5th instar and adults to grains and seeds, and the expected maximum numbers of samples in order to take the decision were 23 and 29 to grains and seeds

Os percevejos são os principais insetos pragas da cultura da soja, e dentre as espécies responsáveis por causarem redução na produtividade e na qualidade dos grãos, destaca-se a espécie Piezodorus guildinii. O objetivo deste trabalho foi determinar a distribuição espacial dos diferentes instares ninfais e da fase adulta de P. guildinii em uma cultivar de soja transgênica RR, e elaborar planos de amostragem sequencial para grãos e sementes. O experimento foi conduzido no ano agrícola 2012/2013, em Jaboticabal, SP, numa área de 30 ha, onde foi selecionado um campo de 10.000 m2, subdividido em 100 parcelas de 10 m x 10 m. A cultivar utilizada foi a SYN 9070 RR, tolerante a herbicida. Nas amostragens foram anotados o número de ninfas do 1o ao 5º instar e o número de adultos por metro em duas linhas de plantio, pelo método da “batida de pano”. Para o estudo da dispersão dos insetos na área, foram utilizados os seguintes índices: razão variância/média, índice de Morisita, coeficiente de Green e expoente k da distribuição binomial negativa. Para o estudo dos modelos probabilísticos que descrevem a distribuição espacial dos insetos, foram testados os ajustes às distribuições de Poisson e binomial negativa. Ninfas de 1º ao 3º instares, 3º instar, 4º e 5º instares, adultos e 4º e 5º intares mais adultos, apresentaram distribuição agregada. No teste de ajuste às distribuições de probabilidade, a distribuição binomial negativa apresentou um bom ajuste para ninfas e adultos de P. guildinii. Foram desenvolvidos planos de amostragem seqüenciais para percevejos de 4º e 5º instar ninfal e adultos para grãos e sementes, e os números máximos de amostras esperados para se tomar a decisão foram de 23 e 29 para grãos e sementes, respectivamente
Keywords: Soja; Soja - Doenças e pragas; Distribuição binomial; Percevejo (Inseto); Hemiptera; Dispersão; Dispersion